Cursed - Meyer, Marissa (Feiwel and Friends, 2022)
Serilda and Gild are in a race against time to break the curses that bind their spirits to Adalheid Castle and to solve the mystery of Gild's forgotten name and past. But they soon realize that the Erlking's desire to bring his one true love back from the Underworld isn't the only thing he wants Serilda's help with. He also seeks vengeance against the seven gods who have long trapped the Dark Ones behind the veil, and if he succeeds, he may doom the entire mortal realm.